2016
DOI: 10.1371/journal.ppat.1005424
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Herpesvirus Utilizes Stress-Induced Cell Cycle Checkpoints for Efficient Lytic Replication

Abstract: Kaposi’s sarcoma herpesvirus (KSHV) causes Kaposi’s sarcoma and certain lymphoproliferative malignancies. Latent infection is established in the majority of tumor cells, whereas lytic replication is reactivated in a small fraction of cells, which is important for both virus spread and disease progression. A siRNA screen for novel regulators of KSHV reactivation identified the E3 ubiquitin ligase MDM2 as a negative regulator of viral reactivation. Depletion of MDM2, a repressor of p53, favored efficient activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 79 publications
1
35
0
Order By: Relevance
“…This KSHV-induced DDR appeared to be essential for latent gene expression and episome replication [66]. In addition, we and others have reported that in different KSHV-infection models the DDR is instigated upon lytic reactivation [67][68][69], thus suggesting that the virus replication induces a genomic stress that might represent a driving force in tumorigenesis or that DDR could provide a favorable host cell environment for efficient virus replication.…”
Section: Contribution Of the Dna Damage Response (Ddr) To Kshv Pathobmentioning
confidence: 78%
“…This KSHV-induced DDR appeared to be essential for latent gene expression and episome replication [66]. In addition, we and others have reported that in different KSHV-infection models the DDR is instigated upon lytic reactivation [67][68][69], thus suggesting that the virus replication induces a genomic stress that might represent a driving force in tumorigenesis or that DDR could provide a favorable host cell environment for efficient virus replication.…”
Section: Contribution Of the Dna Damage Response (Ddr) To Kshv Pathobmentioning
confidence: 78%
“…In fact, this direct relationship between Rta’s relative potency and transfection efficiency was also observed in two other examples in which Rta was stably and uniformly expressed in human cells. (Balistreri et al, 2016; Myoung and Ganem, 2011; Nakamura et al, 2003). In B cells stably transfected with inducible Rta, lytic gene expression was more powerful and efficient upon direct induction of Rta, rather than treatment with HDACis (Nakamura et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In B cells stably transfected with inducible Rta, lytic gene expression was more powerful and efficient upon direct induction of Rta, rather than treatment with HDACis (Nakamura et al, 2003). Furthermore, human (SLK) cells stably infected with KSHV containing inducible Rta do not reactivate upon addition of HDACis alone (Balistreri et al, 2016). Instead, induction of Rta expression leads to low levels of reactivation which are enhanced by further addition of HDACis (Balistreri et al, 2016; Myoung and Ganem, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Kaposi’s sarcoma herpesvirus (KSHV) activates host p53 signal and induces G2 phase arrest to promote the onset of virus replication [6]. Prototype foamy virus (PFV) promotes p53 level increase by knockdown of Pirh2 to contribute to the latency of PFV infection [7].…”
Section: Introductionmentioning
confidence: 99%